MO759: Indoxyl-Sulfate Activation of the AhR-NFΚB Pathway Promotes IL-6 Secretion and Subsequent Osteogenic Transition and Calcification of Interstitial Cells of the Aortic Valve. (3rd May 2022) - Candellier, Alexandre; Boudot, Cedric; Grissi, Maria; Issa, Nervana; Brouette, Théo; Avondo, Carine; Gomila, Cathy; Bennis, Youssef; Touati, Gilles; Caus, Thierry; Choukroun, Gabriel; Brazier, Michel; et al.
Abstract: BACKGROUND AND AIMS: Calcific aortic valve disease (CAVD) results from fibro-calcific degeneration of the aortic valve leaflets, causing haemodynamic disorders and major cardiovascular complications. In chronic kidney disease (CKD) patients, this pathological remodelling is more frequent, appears earlier, progresses more rapidly and leads to a mortality rate three times higher than in the general population. The uremic toxin indoxyl-sulfate (IS) is a powerful predictor of cardiovascular mortality in CKD patients and a strong promoter of aortic calcification. However, its role in aortic valve leaflets mineralization has never been studied. This work aimed to evaluate whether IS can influence the mineralization of primary human valvular interstitial cells (hVICs) cultured in vitro . METHOD: Primary hVICs were isolated from aortic tricuspid valves collected from patients with CAVD undergoing valve replacement surgery at the Amiens Picardie University Hospital. The concentrations of IS used in this study were selected according to the EUTOX registry: IS normal [Isn]: 0.5 µg/mL, IS uremic [Isu]: 37 µg/mL and IS maximum [Ismax]: 233 µg/mL. Human VICs mineralization were induced by exposure to an osteogenic medium containing 2.4 mmol/L calcium and 2.5 mmol/L phosphate (pro-calcific condition) and quantified by the o-cresolphthalein complexone method. The osteogenic transition of hVICs was assessed by qRT-PCR following Bmp2 and Runx2 mRNA expression. The cells' inflammatory potential was assessed by qRT-PCR and ELISA following IL-1β, IL-6 and TNF-α expression and secretion. Activation of NFkB pathway was studied by analysing the phosphorylation of P65 via western blot. A siRNA approach was used to determine the signaling pathway involved in the effects of IS. RESULTS: In pro-calcific conditions, IS increased hVICs osteogenic transition and calcification in a concentration-dependent manner, an effect that was blocked in hVICs transfected with siRNA targeting AhR expression. Data obtained by western blot showed that the exposure to [ISu] and [ISmax] promoted P65 phosphorylation in an AhR dependent manner. Blockade of the NFкB pathway with siRNA targeting P65 inhibited IS-induced expression of Bmp2 and RunX2 as well as hVICs mineralization, suggesting that hVICs inflammation plays a key role in the procalcific effects of IS. Confirming this hypothesis, the exposure to [ISu] and [ISmax] increased the expression of IL-1β, IL-6 and TNF-α transcripts, an effect abolished by silencing AhR and P65. Interestingly, hVICs did not secrete TNF-α and produced only a very low quantity of IL-1β in response to IS. By contrast, the exposure to [ISu] and [ISmax] induced an important release of IL-6 in hVICs culture medium, which was blocked when AhR and P65 were silenced. In this model, the use of an antibody neutralizing IL-6 completely abolished IS-induced hVICs osteogenic transition and calcification. CONCLUSION: Our study demonstrates that IS displays direct pro-calcific effects on primary hVICs through AhR-dependent activation of the NFkB pathway and subsequent release of IL-6. We report that the autocrine action of IL-6 is responsible for IS-induced hVICs osteogenic transition and calcification. The observation that antibodies neutralizing IL-6 can block IS pro-calcific effects might be of particular interest knowing that interventional studies evaluating the cardiovascular impact of anti-IL-6 antibodies in patients with CKD are underway.